The Effect Of Discovery Learning Model On The Science Competency Of Students (Literature Studies From Various Sources) - chelvika ariati; Yurnetti Yurnetti (Department of Science Education, 2022)
Natural Science (IPA) is one of the subjects at the junior high school level, generally taught as an integrated science that studies living things physically and chemically. The main problem is that the competence of students in learning has not been achieved. This could be further improved through applying from discovery models. The goal of this study was to analyze and describe the impact of practicing discovery learning education on student academic competence based on grade at junior high schools, based on learning outcomes, and based on the subject matter. This study including a qualitative descriptive study put on a meta-analysis method. Discovery learning model is effectively used to improve the competence of students based on the class level in junior high school. It can be seen from the effect size value is the effect of discovery learning model on students science competence is 1.33 in a very high category, which means that the discovery learning model has a great effect on increasing competence of students and the use of discovery learning models for subject matter have a great influence, especially on the subject of hydrostatic pressure and Archimedes law.